2016
DOI: 10.1115/1.4032522
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Laser Microtextured Surface Bonded With Composite Solid Lubricant at High Temperature

Abstract: A combination technology of the solid lubricant and the laser surface texturing (LST) can significantly improve the tribological properties of friction pairs. The plate sample was textured by fiber laser and composite lubricant of polyimide (PI) and molybdenum disulfide (MoS 2 ) powders were filled in the microdimples. Sliding friction performances of micron-sized composite lubricant and nano-sized composite lubricant were investigated by ring-plate tribometer at temperatures ranging from room temperature (RT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The most common layered material used in combination with texturing is MoS2. However, studies have been performed on WS2 [241,[245][246][247][248], WS2/Zr [245,249], Cr-WS2 [250], graphite/graphene/carbon-nanotubes (CNTs) [167,233,240,[251][252][253][254][255] , CaF2 [248,256], and hBN [248]. Images of textured surfaces coated with MoS2 and graphite are shown in Figure 15.…”
Section: D Layered Materials and Surface Texturesmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common layered material used in combination with texturing is MoS2. However, studies have been performed on WS2 [241,[245][246][247][248], WS2/Zr [245,249], Cr-WS2 [250], graphite/graphene/carbon-nanotubes (CNTs) [167,233,240,[251][252][253][254][255] , CaF2 [248,256], and hBN [248]. Images of textured surfaces coated with MoS2 and graphite are shown in Figure 15.…”
Section: D Layered Materials and Surface Texturesmentioning
confidence: 99%
“…The inconsistencies in results from comparisons between graphitic materials and MoS2 are likely due to the environment sensitivity of these two materials, since MoS2 performs better in vacuum and graphite better in air. Moreover, studies have combined multiple solid lubricants, as done in studies of textures with MoS2/graphite/Sb2O3 [235], Mo/MoS2/Ag [163] and MoS2/CNTs [253]. Lastly, studies have evaluated the effect of the initial size of solid lubricant particles before application to texture and found that nanoscale MoS2 or graphite particles yield lower friction than the same material deposited in the form of microscale particles [253,255].…”
Section: D Layered Materials and Surface Texturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Laser surface texturing (LST) was recognized as an effective means of surface engineering to improve the tribological properties of sliding surfaces [14,15,16,17,18]. A combination of LST and solid lubricants was utilized to achieve friction reduction and extension on wear resistance life, as micro-dimples can reduce the contact area and protect lubricants in the pit from wear [19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%